Pengembangan Media Pembelajaran Kamus Digital Bahasa Arab terhadap Motivasi Belajar Bahasa Arab Siswa MTs Kelas VIII - Rochim, Amelia Nur; Mubasyiroh, Nabilatun; Annisa, Annisa; Hasby, Muh. Subky (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2025)
Currently, the world of education has various problems, one of which is the learning process, especially the monotonous Arabic language subject. This makes students less interested in the learning process. So that in the learning process requires new innovations such as the use of learning media that attract students' attention and also make it easier for students to learn Arabic. One suitable learning media is a digital dictionary that contains vocabulary in Arabic language textbooks. Therefore, this study aims to develop learning media in the form of a digital dictionary